2015
DOI: 10.1007/s10067-015-3129-1
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between disease activity and hearing impairment in patients with rheumatoid arthritis compared with controls

Abstract: The characteristics of hearing impairment (HI) in rheumatoid arthritis (RA) are still poorly understood, and their association with disease activity is based on conflicting information. This study compared HI between RA patients and controls and between active and remission RA groups using multi-frequency audiometry. This study enrolled 88 RA patients and 50 controls. The pure-tone hearing thresholds at 500 to 4000 Hz for air (AC) and bone (BC) conduction were compared between RA and controls as well as betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 15 publications
2
11
0
Order By: Relevance
“…Cochlear-type sensorineural hearing impairment, including RA, has been reported to specifically affect the lower-frequency hearing ability [ 7 ]. By contrast, other studies reported that RA is associated with high-frequency hearing impairment [ 24 , 25 ]. Considering that adjustment of comorbid conditions was not performed in this study, interpretation of our data has limitation.…”
Section: Discussionmentioning
confidence: 78%
“…Cochlear-type sensorineural hearing impairment, including RA, has been reported to specifically affect the lower-frequency hearing ability [ 7 ]. By contrast, other studies reported that RA is associated with high-frequency hearing impairment [ 24 , 25 ]. Considering that adjustment of comorbid conditions was not performed in this study, interpretation of our data has limitation.…”
Section: Discussionmentioning
confidence: 78%
“… 4–6 With respect to the auditory system, previous studies have shown conflicting findings, in both hearing loss (HL) and the RA disease activity and severity. 7–10 …”
Section: Introductionmentioning
confidence: 99%
“…The hearing impairment at high frequencies may be due to vasculitis/neuritis that affects the cochlea and cochlear nerve leading to SNHL in RA patients. On the contrary to the studies revealed a positive correlation between RA and hearing impairment ( Lasso de la Vega et al., 2016 , Yildirim et al., 2016 , Jeong et al., 2016 ), Lobo FS and Rahne T in separate case control studies did not find statistically significant increase in the incidence of hearing impairment in patients with RA compared to the control groups ( Lobo et al., 2016 , Rahne et al., 2017 ). Besides, Ahmadzadeh A in a case control study of 42 RA patients compared to the age- and sex-matched healthy individuals demonstrated a significantly higher bone conduction threshold in the patients with RA in low frequencies and in the mean of 500–2000 Hz frequencies.…”
Section: Characteristic Of Hearing Impairmentmentioning
confidence: 58%
“…This, however, is not independent of age. A significant association, especially at high frequencies, between hearing impairment and disease activity was detected in a study by Yildirim A, where the audiometric results of 62 patients with active disease was compared with 26 patients in remission ( Yildirim et al., 2016 ). Disease Activity Score in 28 Joints–C-Reactive Protein (DAS28-CRP) was measured based on a count of 28 tender joints, 28 swollen joints, patients global assessment and laboratory result of CRP, which is widely used in clinics ( Yildirim et al., 2016 , Jensen Hansen et al., 2017 ).…”
Section: Ra Disease Characteristic and Hearing Impairmentmentioning
confidence: 97%
See 1 more Smart Citation